Thyroid Feedback Quantile-based Index correlates strongly to renal function in euthyroid individuals - Sijue Yang; Shuiqing Lai; Zixiao Wang; Aihua Liu; Wei Wang; Haixia Guan (Annals of Medicine)
Background Previous studies have reported a negative relationship between thyroid-stimulating hormone (TSH) and renal function in euthyroid individuals, but others have found that higher free thyroxine (FT4) was associated with an increased risk of chronic kidney disease. This study was designed to analyze the relationship between thyroid and renal function from a new perspective of sensitivity to thyroid hormone.Methods This retrospective study included 2831 euthyroid individuals who underwent a health examination at the First Hospital of China Medical University between January 2017 and December 2018. Parametric Thyroid Feedback Quantile-based Index (PTFQIFT4), TSH index (TSHI), thyrotroph T4 resistance index (TT4RI), free triiodothyronine to FT4 ratio (FT3/FT4), the secretory capacity of the thyroid gland (SPINA-GT) and the sum activity of peripheral deiodinases (SPINA-GD) were calculated. We also innovated the TT3RI and PTFQIFT3 indices based on FT3 and TSH. Renal function was assessed by estimated glomerular filtration rate (eGFR) CKD-EPI and creatinine-cystatin C-KDIGO equations.Results After adjustment of basic characteristics and comorbidities, linear regression showed that eGFR CKD-EPI was positively associated with FT3/FT4 (β = 23.31), and inversely correlated to PTFQI FT4 (β= −2.69) (both p < .001). When comparing the fourth versus the first quartile of PTFQI FT4, the odds ratio (OR) for a reduced renal function was 1.89 (95% CI 1.28–2.80), and the OR was 0.64 (95% CI 0.43–0.95) when comparing quartiles of FT3/FT4 (both p for trend< .05). In addition, for every 1SD increase in PTFQI FT4, the OR for a reduced renal function was 1.27 (95%CI 1.10–1.47). TSHI, TT4RI and TT3RI also showed a negative correlation to renal function. Similar results were obtained in SPINA-GD as in FT3/FT4.Conclusions In euthyroid individuals, decreased sensitivity to thyroid hormone is associated with reduced renal function. The composite PTFQIFT4 index correlates more strongly to renal function than TSH or T4 alone.KEY MESSAGESDecreased sensitivity to thyroid hormone is associated with reduced renal function in the euthyroid population.The recently developed composite index PTFQIFT4 seems to correlate more strongly to renal function than individual TSH or FT4 parameters.Innovative indices TT3RI and PTFQIFT3 based on the interaction between T3 and TSH may also reflect sensitivity to thyroid hormone.